2019
DOI: 10.1128/msystems.00325-19
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Compositional and Functional Profiles of Gut Microbiota in Sardinian Centenarians

Abstract: Sardinia, Italy, has a high prevalence of residents who live more than 100 years. The reasons for longevity in this isolated region are currently unknown. Gut microbiota may hold a clue. To explore the role gut microbiota may play in healthy aging and longevity, we used metagenomic sequencing to determine the compositional and functional differences in gut microbiota associated with populations of different ages in Sardinia. Our data revealed that the gut microbiota of both young and elderly Sardinians shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
134
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(166 citation statements)
references
References 91 publications
(136 reference statements)
28
134
2
2
Order By: Relevance
“…We observed that the young and elderly had similar bacterial gut community compositions, consistent with previous studies (21,27), but different from the bacterial gut community composition of most of the centenarians. Similar results were also obtained by our previous metagenomics sequencing (28), as well as the results from an Emilia-Romagna (Italy) cohort and a Japanese cohort (24,26). The separated clustering of the gut bacterial communities in the centenarians across populations suggested that age shaped the gut bacterial community following the same trajectory with the aging process.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We observed that the young and elderly had similar bacterial gut community compositions, consistent with previous studies (21,27), but different from the bacterial gut community composition of most of the centenarians. Similar results were also obtained by our previous metagenomics sequencing (28), as well as the results from an Emilia-Romagna (Italy) cohort and a Japanese cohort (24,26). The separated clustering of the gut bacterial communities in the centenarians across populations suggested that age shaped the gut bacterial community following the same trajectory with the aging process.…”
Section: Discussionsupporting
confidence: 87%
“…Aging-related alterations in the gut bacterial community in different cohorts have been demonstrated in previous studies (20)(21)(22)(23)(24)(25)(26)(27)(28). The variation may be caused by diverse genetic, dietary, and environmental factors (29)(30)(31)(32).…”
mentioning
confidence: 64%
“…Interestingly, L-lysine is an essential ketogenic amino acid and critical building block for proteins. An increase in L-lysine in the human gut was also observed in young compared to centenarian and elderly groups [49]. Our metabolic pathway analysis was done with inferred functional profiles.…”
Section: Discussionmentioning
confidence: 94%
“…Noticeably, the TCA cycle, one of the essential functions of mitochondria [48] and a central hub for energy metabolism and macromolecule synthesis, and pyruvate fermentation to propanoate I were significantly enriched in the old control group. A comparison study of the human gut microbiota between centenarian, elderly and young individuals, based on the premise that centenarians are a model of healthy aging, identified these two metabolic pathways enriched in the centenarian group compared to the young and elderly groups [49]. Since pyruvate is the major precursor for the synthesis of three major SCFAs, acetate, propionate, and butyrate that are related to a strong gut epithelium, this study interpreted the enrichment of the TCA cycle and pyruvate fermentation to propanoate I as a signature of longevity and healthy microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Raw data was rst evaluated by FastQC (version 0.11.8) and mapped against the human genome (hg38) from University of California Santa Cruz (UCSC) with Bowtie2 (version 2.3.5.1), reads aligned to the human genome were removed, and ltered clean reads were used for further analysis. Subsequent analysis was performed as previous study described [44]. Gut microbiotal composition were predicted using MetaPhlan2.0 [45] (version 2.7.7), GraPhlAn (version 0.97) was used to construct the Phylogenetic tree.…”
Section: Bioinformatics Analysismentioning
confidence: 99%